Species composition and ethnobotanical values of karst plants: implications for conservation in Padang Bindu, South Sumatra - Yulizah, Yulizah; Setiawan, Marwan; Sundari, Siti; Handayani, Dewi; Paramita Mukhti, Rizky; Girmansyah, Deden; Efendi, Muhammad; Sunardi; Sadili, Asep; Herlmanto, Hendra (Ethnobotany Research and Applications, 2026)
Background: Karst ecosystems have high biodiversity with important cultural value, but floristic and ethnobotanical studies are limited, including in the Sumatran Karst. Therefore, this research documents plants diversity and utilization used by The Ogan community in the Padang Bindu Karst. Methods: Data were collected using flora inventory and semi-structured interviews. Analysis included Important Value Index (IVI), distribution, conservation status (IUCN), Invasive Alien Species (IAS), ethnobotanical value (Number of Uses [NUs] and Cultural Importance Index [CI]) using R studio software. Results: Padang Bindu Karst has important ecological and socio-economic values. The high biodiversity and community’s dependence on key species emphasizes the urgency of community-based conservation through the protection of economically and culturally valuable species, restoration of native species, and participatory control of IAS. Thus, this research provides an integrative contribution among data floristic, conservation status, invasion, and ethnobotany as a model for community-based conservation in South Sumatra. Conclusions: The communities of the Rwenzori region depend a lot on herbal medicine to treat various diseases irrespective of the availability of modern health care. Keywords: Padang Bindu Karst; Ethnobotany, Use value; Cultural importance index, Community-based conservation